The Sensitive Genes in Response to Various Metal Ion Stresses in the Yeast Saccharomyces cerevisiae - Lyu, Keliang; Shi, Kailun; Liu, Chengkun; Lyu, Zhiwen; Liu, Dongwu; Wang, Xue (Protein and Peptide Letters, 2022)
Yeast Saccharomyces cerevisiae is a good eukaryotic model for studying the molecular mechanism of toxic metal ion stress. Numerous studies have been performed on the signal transduction induced by toxic metal ion stress. The physiological process of eukaryotic cells has been studied, and various stress factors have been elucidated by constructing a gene deletion library. The sensitivity and tolerance mechanism of yeast under metal ion stress has been widely studied. The sensitive genes induced by metal ion stress will provide a key foundation for studying the gene function of eukaryotic organisms. In addition, the functions of genes in response to metal ion stress mainly participate in regulating ion homeostasis, high glycerin pathway, vacuole protein separation pathway, cell wall integrity pathway, and cell autophagy. However, the interaction of these signal pathways and the detailed response mechanism need to be further studied. In addition, the technique of genomics and proteomics will help study the detailed molecular mechanism induced by toxic metal ion stress. Thus, the sensitive genes related to various signal pathways under toxic metal ion stress will be reviewed in the yeast S. cerevisiae.
Keywords: Yeast